2021
DOI: 10.1038/s41559-021-01428-w
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of tumour containment

Abstract: Recent studies have shown that a strategy aiming for containment, not elimination, can control tumour burden more effectively in vitro, in mouse models, and in the clinic. These outcomes are consistent with the hypothesis that emergence of resistance to cancer therapy may be prevented or delayed by exploiting competitive ecological interactions between drug-sensitive and resistant tumour cell subpopulations. However, although various mathematical and computational models have been proposed to explain the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
97
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 40 publications
2
97
0
1
Order By: Relevance
“…While the first two are strictly qualitative, the last type can also be quantitative in terms of the amount of testosterone produced. Strictly qualitative resistance traits have been explored in detail by modelers (You et al, 2017;Zhang et al, 2017;West et al, 2018;Cunningham et al, 2020;Bayer et al, 2021;Kim et al, 2021;Viossat and Noble, 2021), strictly quantitative less so (Staňková et al, 2019;Reed et al, 2020;Wölfl et al, 2020), and the combination, to our knowledge, has not been explored at all. Our models can be used to consider all three contexts (strictly qualitative, strictly quantitative or both).…”
Section: Modeling Eco-evolutionary Dynamics Of Cancer In Response To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While the first two are strictly qualitative, the last type can also be quantitative in terms of the amount of testosterone produced. Strictly qualitative resistance traits have been explored in detail by modelers (You et al, 2017;Zhang et al, 2017;West et al, 2018;Cunningham et al, 2020;Bayer et al, 2021;Kim et al, 2021;Viossat and Noble, 2021), strictly quantitative less so (Staňková et al, 2019;Reed et al, 2020;Wölfl et al, 2020), and the combination, to our knowledge, has not been explored at all. Our models can be used to consider all three contexts (strictly qualitative, strictly quantitative or both).…”
Section: Modeling Eco-evolutionary Dynamics Of Cancer In Response To Treatmentmentioning
confidence: 99%
“…We will also, at times, consider a 20% reduction in tumor volume as the switch threshold. While this has not been tried in any clinical trial, we include it as several authors have shown that it gives superior results as compared to a 50% reduction (Kim et al, 2021;Strobl et al, 2021;Viossat and Noble, 2021).…”
mentioning
confidence: 99%
“…Indeed, a high cell turnover amplifies the effect of competition and therefore the benefits of adaptive therapy. In another study, Viossat et Noble simulated tumors' response to treatment without assuming any costs of resistance, and in spite of that, adaptive therapy was still predicted to outperform MTD-based treatment strategies [43]. Once again, the nature of resistance costs matters, but overall the presence of costs of resistance tends to increase clinical gains.…”
Section: Improving the Modelsmentioning
confidence: 99%
“…Additionally, some ecological phenomena and/or stochasticity events could contribute to making adaptive therapy effective, even without a resistance cost. In brief, it seems that a fitness cost of resistance is not absolutely necessary for adaptive therapy to work, but is certainly helpful [33,43].…”
Section: Improving the Modelsmentioning
confidence: 99%
“…As proposed by Kam et al [ 23 ], alternating a fake drug (called ersatzdroges) with a real drug may allow keeping the tumor size constant, without resistance selection. Interestingly, a close strategy promoting tumor containment has been recently proposed by Viossat and Noble [ 24 ] to avoid, or delay, tumor resistances.…”
mentioning
confidence: 99%